THE RELATIONSHIP BETWEEN LEGAL UNDERSTANDING, ATTITUDES AND DENTIST’S BEHAVIOR ON COMPLETING MEDICAL RECORDS IN SEMARANG - Tahta Danifatis Sunnah; Erdianto Setya Wardhana; hayyu bondan aurora (ODONTO : Dental Journal, 2021)
Background: Medical records according to the Regulation of the Minister of Health of the Republic of Indonesia number 269 / MENKES / PER / III / 2008 are files containing notes and documents concerning identity, examination, treatment, actions, and other services that have been provided to patients. Medical records are also used as written evidence of all service actions and as legal protection for patients, hospitals and doctors and other health workers. Method: This study aims to determine the relationship between dentist legal understanding, attitudes and behavior on the completeness of filling out medical records in Semarang City. This type of research was analytic observational using a cross sectional study. The subjects of this study were dentists who graduated from 2017 to 2019. The samples were selected according to the inclusion criteria obtained from the clinic concerned. Result: The results showed that the writing of the completeness of medical records included in the incomplete category was 20 dentist respondents, 25 dentist respondents in the incomplete category, and no dentist who filled out the complete medical record. Conclusion: There is a relationship between legal knowledge and attitudes of dentists towards completeness of filled in medical records and there was no relationship between dentist behaviour and completeness of filling in medical records.